Predicting movement in architectural space - Aknar, Mustafa; Atun, Resmiye A. (Taylor & Francis Ltd, 2017)
This paper argues that the evaluation of architectural spaces as numerical entities can identify seemingly random patterns of movement behaviour. Built upon analytical theories of space syntax that can produce spatially relevant numerical values, it is proposed that, by analysing integration values from space syntax analysis with a Fibonacci mathematical sequence, it is possible to differentiate social importance between a majority of spaces that are neither segregated nor integrated. Numerical analysis is conducted through a finance tool; Fibonacci retracement calculator. For the application of proposed methodology, a restaurant is chosen as a large public architectural space of social activity. The architectural plan is analysed with space syntax tools and the resulting values entered into a Fibonacci calculator; tracking results with the values of space syntax graph revealed several locations with mediocre values. The resulting spaces are re-evaluated using real-life financial data from the restaurant and employee interviews, the findings correlated with the Fibonacci analysis results; indicated spaces were among the most active tables within the restaurant, following those located directly at integration centres. The results indicate that it is in fact possible to produce accurate predictions of increased social activity among architectural spaces of insignificance as informed by space syntax analysis.
Keywords: Space syntax; spatial analysis; social activity; movement behaviour; Fibonacci